2001
DOI: 10.1679/aohc.64.159
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of Aquaporin-8 in Rat Digestive Organs and Testis.

Abstract: Expression of aquaporin-8 mRNA has previously been shown in hepatocytes, pancreatic acinar cells, colon epithelial cells and seminiferous tubules of the testis in the rat by in situ hybridization technique. However, immunolocalization of this water channel has not yet been demonstrated. In the present study, the localization of immunoreactive aquaporin-8 and expression of the mRNA were examined in rat organs (cerebrum, cerebellum, eye, salivary gland, heart, lung, liver, pancreas, esophagus, stomach, jejunum, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
4

Year Published

2001
2001
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 22 publications
1
61
4
Order By: Relevance
“…We and others have recently shown that rat hepatocytes express mRNA and protein for AQP0 [16] , AQP8 [16][17][18][19][20] , AQP9 [16,21,22] and AQP11 [6] . In addition, other cells of the hepatobiliary tract such as cholangiocytes, gallbladder epithelia and peribiliary vascular endothelia also express AQPs [23][24][25][26][27] .…”
Section: Hepatocyte Aqps: Expression and Subcellular Localizationmentioning
confidence: 99%
“…We and others have recently shown that rat hepatocytes express mRNA and protein for AQP0 [16] , AQP8 [16][17][18][19][20] , AQP9 [16,21,22] and AQP11 [6] . In addition, other cells of the hepatobiliary tract such as cholangiocytes, gallbladder epithelia and peribiliary vascular endothelia also express AQPs [23][24][25][26][27] .…”
Section: Hepatocyte Aqps: Expression and Subcellular Localizationmentioning
confidence: 99%
“…d-cAMP caused a significant increase in canalicular secretion, and this effect could be completely abrogated by both Me 2 SO and phloretin. *, p Ͻ 0.05. sion has also been demonstrated on the luminal side of seminiferous tubules, the apical membrane of pancreatic acinar cells, and in both absorptive epithelia of the colon and acinar cells of the salivary gland; whether AQP8 in these tissues is also regulated by a trafficking mechanism has not been explored (10,(33)(34)(35)(36).…”
Section: Fig 7 D-camp-induced Bile Secretionmentioning
confidence: 99%
“…2 Rat hepatocytes express 3 members of the AQP family of proteins: AQP8, AQP9, and AQP0. [3][4][5][6][7][8][9][10] AQP8, which seems to be the most abundant AQP in hepatocytes, is predominantly localized in intracellular vesicles; its translocation to the canalicular plasma membrane is microtubule dependent and adenosine 3Ј,5Ј-cyclic monophosphate (cAMP) stimulated. 5,6,10 AQP9 resides exclusively on the sinusoidal plasma membranes of hepatocytes and thereby may facilitate the movement of water and certain small solutes.…”
mentioning
confidence: 99%